Is the Gut Microbiome Implicated in the Excess Risk of Hypertension Associated with Obstructive Sleep Apnea? A Contemporary Review - Sanah S. Munir; Fatima H. Sert Kuniyoshi; Prachi Singh; Naima Covassin (MDPI AG, 2023)
Obstructive sleep apnea (OSA) is a highly prevalent sleep disorder and an established risk factor for cardiovascular diseases, including hypertension. The pathogenesis of elevated blood pressure (BP) in OSA is multifactorial, including sympathetic overdrive, vascular aberrations, oxidative stress, inflammation, and metabolic dysregulation. Among the mechanisms potentially involved in OSA-induced hypertension, the role of the gut microbiome is gaining increasing attention. Perturbations in the diversity, composition, and function of the gut microbiota have been causally linked to numerous disorders, and robust evidence has identified gut dysbiosis as a determinant of BP elevation in various populations. In this brief review, we summarize the current body of literature on the implications of altered gut microbiota for hypertension risk in OSA. Data from both preclinical models of OSA and patient populations are presented, and potential mechanistic pathways are highlighted, along with therapeutic considerations. Available evidence suggests that gut dysbiosis may promote the development of hypertension in OSA and may thus be a target for interventions aimed at attenuating the adverse consequences of OSA in relation to cardiovascular risk.